Epistemic Injustice in Islamic Religious Education: A Critical Literature Review in the Digital Media Context - Syahri Harendi (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2026)
The rapid development of digital technology has significantly transformed how religious knowledge is accessed, produced, and disseminated among students. In the context of Islamic Religious Education (IRE), this transformation raises critical concerns regarding epistemic authority, credibility, and the validation of religious knowledge sources in digital environments. This study aims to analyze the phenomenon of epistemic injustice in Islamic education within the digital era, particularly focusing on the shifting relationship between teachers, students, and digital media. This research employs a qualitative approach using a critical literature review method. Data were collected from reputable academic databases such as Scopus, Google Scholar, and SINTA-indexed journals, with inclusion criteria focusing on publications from 2015–2025 related to epistemic injustice, Islamic education, and digital media. Thematic analysis was employed to identify recurring patterns, conceptual relationships, and epistemological implications. The findings reveal three major forms of epistemic injustice the shift of epistemic authority from teachers to digital platforms, the delegitimization of teachers as credible religious knowledge sources, and he fragmentation of students’ religious understanding due to unverified and algorithm-driven digital content. The study’s novelty lies in integrating epistemic injustice theory with Islamic epistemological principles such as tabayyun (verification) and tafakkur (critical reflection) as conceptual solutions for strengthening epistemic literacy in Islamic Religious Education in the digital era.